Super Enhancer-Regulated LINC00094 (SERLOC) Upregulates the Expression of MMP-1 and MMP-13 and Promotes Invasion of Cutaneous Squamous Cell Carcinoma - Piipponen Minna; Riihilä Pilvi; Knuutila Jaakko S; Kallajoki Markku; Kähäri Veli-Matti; Nissinen Liisa (MDPI, 2025)
Simple Summary
Cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer, and its incidence is increasing worldwide. The prognosis of the metastatic disease is poor, and there are no established biomarkers for the assessment of metastasis risk or specific therapeutic targets for advanced or metastatic cSCCs. The role of long non-coding RNAs (lncRNAs) in the progression of cSCC has recently been emphasized. Super enhancers (SE) have been shown to play a role in tumorigenesis and regulate the expression of specific lncRNAs. In this study, we evaluated the role of SE-regulated BRD3OS (lncRNA LINC00094) in the progression of cSCC. Based on the results, we named this lncRNA SERLOC. The results identify SERLOC as a biomarker for invasion and metastasis of cSCC and as a putative therapeutic target in advanced cSCC.
Long non-coding RNAs (lncRNAs) have emerged as important regulators of cancer progression. Super enhancers (SE) play a role in tumorigenesis and regulate the expression of specific lncRNAs. We examined the role of BRD3OS, also named LINC00094, in cutaneous squamous cell carcinoma (cSCC). Elevated BRD3OS (LINC00094) expression was detected in cSCC cells, and expression was downregulated by SE inhibitors THZ1 and JQ1 and via the MEK1/ERK1/2 pathway. Increased expression of BRD3OS (LINC00094) was noted in tumor cells in cSCCs and their metastases compared to normal skin, actinic keratoses, and cSCCs in situ. Higher BRD3OS (LINC00094) expression was noted in metastatic cSCCs than in non-metastatic cSCCs. RNA-seq analysis after BRD3OS (LINC00094) knockdown revealed significantly regulated GO terms Cell-matrix adhesion, Basement membrane, Metalloendopeptidase activity, and KEGG pathway Extracellular matrix-receptor interaction. Among the top-regulated genes were MMP1, MMP10, and MMP13. Knockdown of BRD3OS (LINC00094) resulted in decreased production of MMP-1 and MMP-13 by cSCC cells, suppressed invasion of cSCC cells through collagen I, and growth of human cSCC xenografts in vivo. Based on these observations, BRD3OS (LINC00094) was named SERLOC (super enhancer and ERK1/2-Regulated Long Intergenic non-protein coding transcript Overexpressed in Carcinomas). These results reveal the role of SERLOC in cSCC invasion and identify it as a potential therapeutic target in advanced cSCC.